A comparison of work culture between some European countries and Turkey - (:unkn) unknown (Inderscience Publishers, 2015)
Multi-criteria decision making (MCDM) methods can be applied to social areas as well as economical and industrial areas. By using MCDM, we will obtain some social outcomes from this field. In this study, we analyse and compare some countries and Turkey in terms of specific aspects of the work culture and ethics by using the PROMETHEE method, a MCDM. The objective of the European Union (EU) is to achieve economic, politic and social integration. In this respect, work culture is an important dimension of social harmonisation and integration. Results of the study show that there are no homogenisation and harmonisation among Turkey and some of the countries considered. Turkey is distinguished from the other European countries in terms of gender and immigrant discrimination in the working life. Copyright © 2015 Inderscience Enterprises Ltd.
Keywords: MCDM; Multi-criteria decision making; PROMETHEE method; Turkey; Work culture